Homology modeling and molecular dynamics provide structural insights into tospovirus nucleoprotein. Issue 18 (December 2016) - Lima, Rayane; Faheem, Muhammad; Barbosa, João; Polêto, Marcelo; Verli, Hugo; Melo, Fernando; Resende, Renato
Abstract Background Tospovirus is a plant-infecting genus within the family Bunyaviridae, which also includes four animal-infecting genera: Hantavirus, Nairovirus, Phlebovirus and Orthobunyavirus. Compared to these members, the structures ofTospovirus proteins still are poorly understood. Despite multiple studies have attempted to identify candidate N protein regions involved in RNA binding and protein multimerization for tospovirus using yeast two-hybrid systems (Y2HS) and site-directed mutagenesis, the tospovirus ribonucleocapsids (RNPs) remains largely uncharacterized at the molecular level and the lack of structural information prevents detailed insight into these interactions. Results Here we used the nucleoprotein structure of LACV (La Crosse virus-Orthobunyavirus ) and molecular dynamics simulations to access the structure and dynamics of the nucleoprotein from tospovirus GRSV (Groundnut ringspot virus ). The resulting model is a monomer composed by a flexible N-terminal and C-terminal arms and a globular domain with a positively charged groove in which RNA is deeply encompassed. This model allowed identifying the candidate amino acids residues involved in RNA interaction and N-N multimerization. Moreover, most residues predicted to be involved in these interactions are highly conserved among tospoviruses. Conclusions Crucially, the interaction model proposed here for GRSV N is further corroborated by the all available mutational studies on TSWV (Tomato spotted wilt virus ) N, so far. Our data will help designing further and more accurate mutational and functional studies of tospovirus N proteins. In addition, the proposed model may shed light on the mechanisms of RNP shaping and could allow the identification of essential amino acid residues as potential targets for tospovirus control strategies.